Does Material Adverse Change (MAC) Fulfill the Principles of an Agreement? - Suwinto Johan; Markoni Markoni (Jurnal IUS Kajian Hukum dan Keadilan, 2021)
Material Adverse Change (MAC) clause is rarely discussed in contract law because it is an agreement between the two parties. This clause has quite extensive effects, especially at the time of the Covid-19 Pandemic. This article is generally found in company mergers and acquisitions agreements and credit or financing agreements. MAC Clause will be needed when there is a significant changes in business. This research wants to test whether the Material Adverse Change clause meets the principles’ requirements in a contract or agreement. The research is normative juridical research. This research will refer to the principles in agreement and relating to the definition of Material Adverse Change/Effect (MAC/E). This research concludes that Material Adverse Change is a clause which fulfills the principles in an agreement, especially the principle of the Freedom of Contract, the Principle of Good Balance, the Principle of Consensuality (Agreement/Consensualism), the Principle of Legal Certainty (Facta Sunt Servanda), the Principle of Good Faith, and the Principle of Personality. The MAC should be effective under the Pandemic’s condition.